2013
DOI: 10.3389/fnhum.2013.00904
|View full text |Cite
|
Sign up to set email alerts
|

More than a face: a unified theoretical perspective on nonverbal social cue processing in social anxiety

Abstract: Processing of nonverbal social cues (NVSCs) is essential to interpersonal functioning and is particularly relevant to models of social anxiety. This article provides a review of the literature on NVSC processing from the perspective of social rank and affiliation biobehavioral systems (ABSs), based on functional analysis of human sociality. We examine the potential of this framework for integrating cognitive, interpersonal, and evolutionary accounts of social anxiety. We argue that NVSCs are uniquely suited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 225 publications
2
31
0
Order By: Relevance
“…Likewise, the absence of AB at baseline assessment in several recent ABM studies also raises questions about how common AB is among SAD individuals (e.g., Boettcher et al, 2013;Julian et al, 2012;McNally et al, 2013). It is possible that people develop SAD via pathways other than through AB (e.g., Brühl, Delsignore, Komossa, & Weidt, 2014;Gilboa-Schechtman & Shachar-Lavie, 2013;Haller, Cohen Kadosh, & Lau, 2014;Krimbel, 2008). This way, although early ABM publications in top-tier journals have contributed to reinforce the notion that AB does play an acute causal role in the maintenance of SAD, the present findings call for a critical reconsideration of the importance of AB in the conceptualization of this disorder.…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 94%
“…Likewise, the absence of AB at baseline assessment in several recent ABM studies also raises questions about how common AB is among SAD individuals (e.g., Boettcher et al, 2013;Julian et al, 2012;McNally et al, 2013). It is possible that people develop SAD via pathways other than through AB (e.g., Brühl, Delsignore, Komossa, & Weidt, 2014;Gilboa-Schechtman & Shachar-Lavie, 2013;Haller, Cohen Kadosh, & Lau, 2014;Krimbel, 2008). This way, although early ABM publications in top-tier journals have contributed to reinforce the notion that AB does play an acute causal role in the maintenance of SAD, the present findings call for a critical reconsideration of the importance of AB in the conceptualization of this disorder.…”
Section: Theoretical and Clinical Implicationsmentioning
confidence: 94%
“…During facial emotional categorization, young females with MDD exhibit hyperactivation, whereas young males display hypoactivation in the precuneous brain area, as indicated by fMRI (Briceño et al, ). Several aspects of face processing are also deficient in social anxiety (Gilboa‐Schechtman and Shachar‐Lavie, ). Women but not men with social anxiety are hypersensitive to threat (an avoidance‐related expression) and approval‐related facial emotional expressions such as fear, sadness, and happiness (Arrais et al, ).…”
Section: Sex Differences In Face Processingmentioning
confidence: 99%
“…Anxiety disorders are characterized by abnormal responses to nonverbal social cues, namely increased attention to threatening stimuli (Gilboa-Schechtman & Shachar-Lavie, 2013). Research has found that even in healthy individuals, an increased attentional bias to threat magnifies subsequent anxiety in response to social exclusion (Heeren, Peschard, & Philippot, 2012).…”
Section: Introductionmentioning
confidence: 99%